Legal Remedies for Workers Who Experience Termination of Employment Due to Force Majeure Reasons - Rasji, Rasji (Riwayat: Educational Journal of History and Humanities, 2025)
Industrial relations in Indonesia are based on the principles of Pancasila Industrial Relations, which is a form of relationship between actors in the production process of goods and services, namely workers, employers, and the government. In this study, the researcher focuses on whether the provisions regarding force majeure in Indonesian labor law are in accordance with the principles of fair and sustainable labor protection, by analyzing the extent to which labor law in Indonesia supports worker protection in force majeure situations, and whether existing legal provisions are still relevant to the principle of social justice for workers. In relation to layoffs caused by force majeure reasons, workers have the right to seek legal remedies to obtain protection. According to Law No. 13 of 2003, termination of employment in force majeure situations can be carried out, but must still comply with existing provisions, such as the provision of severance pay and other rights in accordance with applicable provisions. Legal remedies in labor disputes are a crucial aspect in ensuring justice and protection for workers in Indonesia. In the context of industrial relations, disputes between workers and employers often involve issues of basic worker rights, such as wages, working conditions, termination of employment (PHK), or unpaid benefits. Without a clear legal mechanism, workers may not be able to obtain equal justice with employers who have greater access to legal resources. Therefore, legal remedies are an important channel to ensure that workers' rights are maximally protected.